Natural Occurrence of Metarhizium rileyi on Darna diducta as a Biological Control for Oil Palm Pests in Poso, Central Sulawesi - Henny Hendarjanti; Henik Sukorini (Andalasian International Journal of Entomology, 2024)
The nettle caterpillar, Darna diducta, is a significant pest in oil palm plantations, causing damage to palm fronds that impacts overall plant health and yield. Traditionally, synthetic insecticides are used to manage this pest; however, such intensive chemical use has led to adverse effects, including pest resistance, resurgence, and environmental degradation. Entomopathogenic fungi like Metarhizium rileyi (formerly Nomuraea) represent a promising, environmentally friendly alternative for pest control. This study focused on the natural occurrence of M. rileyi infections in D. diducta larvae within oil palm plantations in East Pamona, Poso Regency, Central Sulawesi, observed in August 2015. Surveys conducted across several villages found a remarkable 100% infection rate of D. diducta larvae by M. rileyi, with each infected larva exhibiting extensive fungal growth, characterized by white mycelium covering the entire body. The resulting impact on palm frond damage was minimal, with the percentage of plant damage due to D. diducta categorized as mild, ranging from only 0.24% to 0.34%. These findings indicate that M. rileyi effectively suppresses D. diducta populations, reducing pest severity and frond damage. The high infection rate and its impact on pest control underscore M. rileyi’s potential as a natural biocontrol agent, offering a sustainable approach to managing D. diducta infestations. Thus, integrating M. rileyi as a biological control method could significantly benefit oil palm cultivation by minimizing chemical use, promoting ecological balance, and supporting long-term pest management strategies.